2016
DOI: 10.1039/c5ra22773a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive electrochemical detection of UO22+ based on DNAzyme and isothermal enzyme-free amplification

Abstract: A novel enzyme-free amplification biosensor for uranyl detection was developed based on UO22+-specific DNAzyme and a hybridization chain reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Different amplification strategies, such as hybridization chain reaction (HCR) and catalyzed hairpin assembly (CHA), were used for electrochemical biosensor development. Yun et al reported an ultrasensitive DNAzyme-based electrochemical sensor for uranyl detection ( Yun et al, 2016b ). DNAzyme was selectively cleaved in the presence of UO 2 2+ .…”
Section: Applications Of Different Types Of Dnazyme-based Sensorsmentioning
confidence: 99%
“…Different amplification strategies, such as hybridization chain reaction (HCR) and catalyzed hairpin assembly (CHA), were used for electrochemical biosensor development. Yun et al reported an ultrasensitive DNAzyme-based electrochemical sensor for uranyl detection ( Yun et al, 2016b ). DNAzyme was selectively cleaved in the presence of UO 2 2+ .…”
Section: Applications Of Different Types Of Dnazyme-based Sensorsmentioning
confidence: 99%
“…The initiator opens H2, which subsequently opens H1 to form a nicked dsDNA polymer chain, which is again filled with minor groove binder MB to give an electrochemical signal, with an LOD of 20 pM (Fig. 3B) [64]. It should be noted that a further study uses the formation of a hairpin polymer for the electrochemical detection of Pb 2+ by tethering the enzyme sequence of a DNAzyme to a magnetic bead, and using the cleavage of the substrate and exposure of the enzyme sequence to initiate a hairpin chain assembly on the magnetic beads with a ferrocene-tagged hairpin, generating an electrochemical signal, with an LOD of 37 pM [67].…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…Many analytical methods have been developed for UO 2 2+ detection such as electrochemical methods, 4 fluorescence spectroscopy, 5 UV–vis adsorption spectrometry, 6 ICP mass spectrometry (ICP-MS), 7 inductively coupled plasma atomic emission spectroscopy (ICP-AES), 8 and so on. Despite providing concentration information, those methods lack the capability of enforcing in situ analysis or require time-consuming sample preparation, sophisticated equipment, expert operators, and high cost, limiting their practical applications.…”
Section: Introductionmentioning
confidence: 99%